Le sang et la politique. La production de la famille dans les joutes électorales du Sertão du Pernambouc, Brésil - Marques, Ana Claudia; Villela, Jorge Mattar (Anthropologica, 2017)
Despite the seeming impossibility of attaining a pure form of democracy, one of democracy’s cherished aims is to purify the realm of governance from family interests. In this article, which is based on ethnography collected in Floresta, a municipality located in Pernambuco, Northeast Brazil, we reflect on the manner in which notions of family and politics become at once synonymous in some circumstances. In this context, we suggest, politics and kinship cannot be conceptualised as autonomous domains. Through an exploration of family categories, we identify three circumstances of crisis in which blood and politics are inextricably linked.